In-situ coated reinforced silane crosslinked chloroprene rubber composite

CN122917408APending Publication Date: 2026-10-16GUANGZHOU MEICUN RUBBER TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611202532.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]尽管上述现有技术在不同方面对氯丁橡胶进行了改进,但仍存在诸多技术不足:首先,传统的氧化锌/氧化镁金属氧化物硫化体系虽能提供必要的交联密度,但氧化锌等重金属的使用存在环保风险,在产品的生产、使用及废弃处理过程中可能带来重金属迁移与富集问题,难以满足日益严苛的环保法规要求;其次,现有的硅烷交联技术仅改变了交联体系,未解决填料-基体界面问题,在填料处理方面,白炭黑等纳米填料主要通过物理共混方式加入基体,配合硅烷偶联剂进行表面改性,但这种偶联剂处理主要依赖于物理吸附或较弱的物理缠结,填料在基体中的团聚现象难以根本消除,填料与基体之间的界面结合力仍然较弱;再者,由于界面结合不良和填料团聚,复合材料在动态载荷条件下容易产生界面滑移,导致动态生热高、滞后损失大,严重影响减震制品、电缆护套等动态工况下橡胶制品的抗疲劳寿命和使用可靠性

Benefits of technology

(1)本发明通过原位包覆与界面接枝同步进行的工艺,在氯丁橡胶于纳米二氧化硅表面析出包覆的同时,利用壳层氯丁橡胶分子链上的烯丙基氯与巯基硅烷偶联剂的巯基发生亲核取代反应,将烷氧基硅烷基团通过稳定的硫醚键共价接枝于壳层表面。硫化过程中,该接枝的烷氧基硅烷基团与外加硅烷交联剂共同水解缩合,形成Si-O-Si交联桥,使填料壳层与基体之间以共价键连接。相较于传统物理共混中依赖范德华力的弱界面,共价键界面结合能大幅提升,有效抑制纳米填料的迁移与重聚,解决了填料分散性差和界面结合弱的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an in-situ coated reinforced silane cross-linked chloroprene rubber composite material and a preparation method thereof. The composite material comprises a chloroprene rubber matrix and a core-shell structure reinforcing filler, wherein nano silicon dioxide is used as the core, chloroprene rubber is used as the shell, and the shell layer is grafted with alkoxy silane groups derived from mercapto silane coupling agents through a sulfide bond; the rubber matrix and the filler are covalently connected through a siloxane cross-linked network formed by the alkoxy silane groups. The preparation method comprises the following steps: pre-grafting mercapto silane coupling agents on the surface of nano silicon dioxide, mixing the nano silicon dioxide with chloroprene latex, and performing alcohol precipitation to precipitate the chloroprene rubber and simultaneously react with mercapto groups, so as to obtain core-shell fillers with reactive silane groups on the surface; and mixing the core-shell fillers with chloroprene rubber and additional silane cross-linking agents, and then performing two-stage vulcanization to obtain the product. The silane cross-linking system is used to replace metal oxide vulcanization, the agglomeration of fillers is inhibited through covalent bond interface connection, dynamic heat generation is reduced, and the unification of environmental protection and performance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chloroprene rubber technology, and more particularly to an in-situ coated reinforced silane crosslinked chloroprene rubber composite material. Background Technology

[0002] Chloroprene rubber (CR) is a high-molecular-weight elastomer produced by emulsion polymerization of 2-chloro-1,3-butadiene as the main monomer. Its unique allyl chloride structure in the molecular chain endows the material with excellent oil resistance, abrasion resistance, weather resistance, ozone aging resistance, and flame retardant properties, making it widely used in the automotive industry, aerospace, wire and cable sheathing, sealing products, and vibration damping components. To meet the performance requirements of different applications, chloroprene rubber typically requires cross-linking to form a three-dimensional network structure for optimal performance. Its reactivity is relatively low, and its vulcanization system differs significantly from that of natural rubber and styrene-butadiene rubber. It primarily employs a metal oxide vulcanization system, supplemented by specific accelerators.

[0003] In the vulcanization and crosslinking technology of chloroprene rubber, metal oxide vulcanization is the most commonly used method. For example, patent documents such as CN115322462B disclose a technical solution using zinc oxide and magnesium oxide as vulcanizing agents for chloroprene rubber. Zinc oxide provides zinc ions that abstract allyl chloride from the 1,2-polymer side groups of the chloroprene rubber molecule, causing the molecular chains to undergo a crosslinking reaction and form a stable crosslinked network. Simultaneously, to further improve the mechanical and processing properties of chloroprene rubber, existing technologies extensively use nanofillers such as silica for reinforcement, and combine them with silane coupling agents to modify the surface of the fillers to improve dispersibility. Furthermore, to avoid the high energy consumption problem of traditional metal oxide vulcanization systems, CN104821197B also proposes a silane crosslinking method that involves mixing chloroprene rubber with organosilane compounds containing amino or mercapto groups, and then contacting it with water in the presence of a silanol condensation catalyst to generate crosslinks.

[0004] Although the aforementioned existing technologies have improved chloroprene rubber in various aspects, they still have many shortcomings: First, while the traditional zinc oxide / magnesium oxide vulcanization system can provide the necessary crosslinking density, the use of heavy metals such as zinc oxide poses environmental risks. Heavy metal migration and accumulation may occur during product manufacturing, use, and disposal, making it difficult to meet increasingly stringent environmental regulations. Second, existing silane crosslinking technologies only change the crosslinking system and do not solve the filler-matrix interface problem. Regarding filler treatment, nanofillers such as silica are mainly added to the matrix through physical blending, combined with silane coupling agents for surface modification. However, this coupling agent treatment mainly relies on physical adsorption or weak physical entanglement, making it difficult to fundamentally eliminate filler agglomeration in the matrix, and the interfacial bonding between the filler and matrix remains weak. Furthermore, due to poor interfacial bonding and filler agglomeration, composite materials are prone to interfacial slippage under dynamic load conditions, resulting in high dynamic heat generation and large hysteresis losses, severely affecting the fatigue life and reliability of rubber products such as shock-absorbing products and cable sheaths under dynamic working conditions. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides an in-situ coated reinforced silane crosslinked chloroprene rubber composite material and its preparation method.

[0006] 1. Composite material technology solutions An in-situ coated reinforced silane crosslinked chloroprene rubber composite material includes a chloroprene rubber matrix and a core-shell structured reinforcing filler dispersed in the chloroprene rubber matrix; The core-shell structure reinforcing filler includes nano-silica as the core and chloroprene rubber as the shell; the shell is grafted with alkoxysilane groups derived from mercaptosilane coupling agents via thioether bonds. The chloroprene rubber matrix and the core-shell structure reinforcing filler are connected through a siloxane crosslinking network formed by the participation of the alkoxysilane groups.

[0007] Furthermore, the mercaptosilane coupling agent is selected from at least one of γ-mercaptopropyltriethoxysilane and γ-mercaptopropyltrimethoxysilane; in the shell layer, the allyl chloride on the chloroprene rubber molecular chain undergoes a nucleophilic substitution reaction with the mercapto group of the mercaptosilane coupling agent to form the thioether bond. This facilitates the covalent connection between the chloroprene rubber molecular chain and the alkoxysilane group in the shell layer, providing a reaction anchor for subsequent co-crosslinking.

[0008] Furthermore, the specific surface area of ​​the nano-silica is 150-200 m². 2 / g. The high specific surface area of ​​nano-silica provides abundant surface silanol groups, which is beneficial for the full grafting of mercaptosilane coupling agents.

[0009] Furthermore, using a chloroprene rubber matrix as a reference, the amount of the core-shell reinforcing filler is 20-60% of the chloroprene rubber matrix mass; the siloxane crosslinking is formed by the co-hydrolysis and condensation of the alkoxysilane groups on the surface of the core-shell reinforcing filler and the added silane crosslinking agent. This co-hydrolysis and condensation mechanism is the key to achieving interfacial co-crosslinking, enabling the filler shell and the matrix to form a through-network through covalent bonds.

[0010] Furthermore, the added silane crosslinking agent is selected from one or a combination of two of vinyltrimethoxysilane and vinyltriethoxysilane.

[0011] 2. Preparation Method Technical Solution A method for preparing the above-mentioned in-situ coated reinforced silane crosslinked chloroprene rubber composite material includes the following steps: Step (1) Pre-modification of filler surface: Nano-silica is dispersed in water, and a mercaptosilane coupling agent is added for pre-hydrolysis to obtain a modified silica dispersion with alkoxysilane groups grafted onto its surface. In this step, the alkoxy groups of the mercaptosilane coupling agent condense with the silanol groups on the surface of the nano-silica, thereby pre-introducing mercapto functional groups onto the silica surface. Preferably, the amount of the mercaptosilane coupling agent is 2%-5% of the dry weight of the nano-silica.

[0012] Step (2) In-situ coating and interface grafting: The modified silica dispersion obtained in step (1) was mixed with chloroprene latex. An alcohol precipitant was added under shear stirring to precipitate chloroprene rubber and coat the surface of nano-silica. The pH was adjusted to 8-9 and the mixture was heated to 50-60℃ for 2-3 hours to obtain a core-shell structured reinforced filler with reactive silane groups on the surface. The process of chloroprene latex demulsification and in-situ precipitation and coating of chloroprene rubber molecular chains on the nano-silica surface initiated by the alcohol precipitant proceeds simultaneously with the nucleophilic substitution reaction between the allyl chloride on the shell chloroprene rubber molecular chains and the mercaptosilane coupling agent.

[0013] Step (3) Mixing: The core-shell reinforcing filler obtained in step (2) is mixed with chloroprene rubber raw rubber, an added silane crosslinking agent, an initiator, and a catalyst at 80-100℃ to obtain a compound. The mixing temperature is controlled at 80-100℃ to ensure that the components are fully dispersed and mixed, while avoiding scorching caused by excessive temperature. Preferably, the initiator is dicumyl peroxide, and the amount used is 1-3% of the chloroprene rubber raw rubber; the catalyst is dibutyltin dilaurate, and the amount used is 0.1-0.5% of the chloroprene rubber raw rubber.

[0014] Step (4) Two-stage vulcanization: The compound obtained in step (3) is first vulcanized at 160-170℃ and 10-15 MPa pressure, and then vulcanized again at 70-95℃ and 70%-95% relative humidity to obtain the in-situ coated reinforced silane crosslinked chloroprene rubber composite material.

[0015] In the primary vulcanization stage, under high temperature, high pressure, and the action of the initiator, the silane crosslinking agent and the alkoxysilane groups on the surface of the core-shell filler undergo hydrolysis and condensation to form a Si-O-Si crosslinking network, achieving covalent bonding between the filler and the matrix. In the secondary vulcanization stage, under a humid and hot environment, the silane groups that were not fully reacted in the primary vulcanization continue to hydrolyze and condense, perfecting the crosslinking network, eliminating internal stress, and stabilizing the material properties.

[0016] Preferably, the secondary vulcanization employs a gradient vulcanization process: first, treatment at 70-75℃ and 90%-95% relative humidity for 6-12 hours, followed by treatment at 85-95℃ and 70%-80% relative humidity for 6-24 hours. This gradient design allows for sufficient moisture penetration, thorough hydrolysis in the low-temperature stage, and accelerated condensation in the high-temperature stage, resulting in a composite material with higher crosslinking density and a more stable structure.

[0017] The beneficial effects of this invention are as follows: (1) This invention employs a process that simultaneously performs in-situ coating and interfacial grafting. While chloroprene rubber is deposited and coated on the surface of nano-silica, the allyl chloride on the chloroprene rubber molecular chain undergoes a nucleophilic substitution reaction with the mercapto group of the mercaptosilane coupling agent, covalently grafting alkoxysilane groups onto the shell surface via stable thioether bonds. During vulcanization, the grafted alkoxysilane groups and the added silane crosslinking agent undergo hydrolysis and condensation to form Si-O-Si crosslinking bridges, connecting the filler shell and the matrix via covalent bonds. Compared to the weak interfaces relying on van der Waals forces in traditional physical blending, the covalent bond interfacial bonding energy is significantly improved, effectively inhibiting the migration and reaggregation of nanofillers and solving the problems of poor filler dispersibility and weak interfacial bonding.

[0018] (2) Because the core-shell filler participates in the matrix crosslinking network through covalent bonds, a through-crosslinking structure is formed between the filler and the matrix. Under dynamic load, interface slippage and friction loss are greatly reduced, and energy dissipation is significantly reduced. The dynamic compression heat generation of the composite material of the present invention is significantly reduced compared with the traditional metal oxide vulcanization system. It is particularly suitable for products such as automobile engine mounts and rail transit vibration damping pads that are subjected to dynamic alternating loads for a long time, and can effectively extend their service life.

[0019] (3) This invention uses a silane crosslinking system to replace the traditional zinc oxide / magnesium oxide sulfide system, eliminating the introduction of heavy metals. However, its environmental friendliness does not come at the expense of performance. The core-shell filler shell is homogeneous with the matrix and co-crosslinked, and stress can be efficiently transferred to the rigid nano-silica core through the covalent bond interface, achieving excellent reinforcement effect. While making the material environmentally friendly, its tensile strength, tear strength and other mechanical properties are still better than those of traditional heavy metal-containing systems, achieving a unity of high performance and greenness. Detailed Implementation

[0020] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.

[0021] Example 1 (1) Pre-modification of filler surface: 100 g of filler with a specific surface area of ​​180 m² 2 / g of nano-silica was added to 1000 mL of deionized water and ultrasonically dispersed for 30 min to obtain a uniform silica suspension. 4 g of γ-mercaptopropyltriethoxysilane was added under stirring, and the pH was adjusted to 4.5 with acetic acid. Stirring and hydrolysis continued for 30 min under a nitrogen atmosphere to obtain a modified silica dispersion with alkoxysilane groups grafted onto its surface.

[0022] (2) In-situ coating and interface grafting: The modified silica dispersion obtained in step (1) was mixed with chloroprene latex containing 30 g of dry rubber (Jinan Chenshuo New Building Materials Co., Ltd., solid content 40%, i.e., emulsion dosage 75 g). Anhydrous ethanol was rapidly poured in at a shear stirring rate of 1200 rpm, so that the volume fraction of ethanol in the system instantly reached 70%. Chloroprene rubber precipitated from the emulsion under the action of ethanol and coated the surface of nano silica. At the same time, the pH of the system was adjusted to 8.5 with sodium carbonate solution, the temperature was raised to 55℃, and the reaction was kept at this temperature for 2.5 hours under continuous shear stirring, so that the allyl chloride on the chloroprene rubber molecular chain coated on the silica surface reacted with the mercapto group of γ-mercaptopropyltriethoxysilane to generate a thioether bond, thereby covalently grafting the alkoxysilane group onto the shell surface. A small amount of the reaction filtrate and product were analyzed using the Ellman reagent method. No free thiol groups were detected, thus ending the reaction. The solid product was separated by centrifugation, washed three times with anhydrous ethanol, and vacuum dried at 40°C to constant weight, yielding a core-shell structured reinforcing filler with reactive silane groups on its surface. FTIR analysis (KBr pellet method) was performed, and compared with unmodified nano-silica: 1100 cm⁻¹ -1 Enhanced Si-O-Si peak at 960 cm⁻¹ -1 The weakening of the Si-OH peak at 2550-2600 cm⁻¹ indicates that the silane coupling agent has been grafted onto the silica surface; -1The SH peak disappears at 690 cm. -1 The appearance of a CSC peak at [value missing] confirms the formation of a thioether bond; a peak at 1665 cm⁻¹ also appears. -1 (C=C) and 825 cm -1 The characteristic peak of (C-Cl) for chloroprene rubber indicates that chloroprene rubber has been successfully coated and covalently bonded to the silica surface.

[0023] (3) Mixing: On a two-roll mill, 100 g of chloroprene rubber (CR244, Chongqing Changshou Jieyuan Chemical Co., Ltd.) was plasticized. After wrapping the rolls, 40 g of the core-shell structure reinforcing filler obtained in step (2) was added, and the mixture was mixed at a roll temperature of 90°C until the filler was evenly dispersed. Then, 4 g of vinyltrimethoxysilane, 2 g of dicumyl peroxide, and 0.3 g of dibutyltin dilaurate were added in sequence, and the mixture was continued to be mixed evenly. The mixture was then sheeted out to obtain the compound.

[0024] (4) Two-stage vulcanization: The compound rubber is placed in the mold of the flat vulcanizing machine and vulcanized at 165°C and 12 MPa. The vulcanization time is the positive vulcanization time (measured by a rotorless vulcanizing instrument at 165°C; in this example, t90 is 11 minutes). After the first stage of vulcanization is completed, the rubber sheet is taken out and placed in a constant temperature and humidity chamber for the second stage of vulcanization: first, it is treated at 75°C and 95% relative humidity for 10 hours, and then the temperature is raised to 90°C and 80% relative humidity for 18 hours to obtain the in-situ coated reinforced silane crosslinked chloroprene rubber composite material.

[0025] Example 2 (1) Pre-modification of filler surface: 100 g of filler with a specific surface area of ​​200 m² 2 / g of nano-silica was added to 1200 mL of deionized water and ultrasonically dispersed for 40 min. 5 g of γ-mercaptopropyltriethoxysilane was added, the pH was adjusted to 4.5 with acetic acid, and hydrolysis was carried out for 30 min to obtain a modified silica dispersion.

[0026] (2) In-situ coating and interfacial grafting: The above dispersion was mixed with chloroprene latex containing 30 g of dry adhesive, and anhydrous ethanol was rapidly added to a volume fraction of 75% under shear stirring at 1500 rpm. The pH was adjusted to 9.0 with sodium carbonate, and the mixture was heated to 60°C and reacted for 3 hours. After centrifugation, washing, and vacuum drying at 40°C, the core-shell structure reinforced filler was obtained.

[0027] (3) Mixing: On a two-roll mill, 100 g of chloroprene rubber raw rubber is plasticized, and 60 g of core-shell structure reinforcing filler is added. The mixture is then mixed evenly at a roll temperature of 100°C. 6 g of vinyltrimethoxysilane, 3 g of dicumyl peroxide, and 0.5 g of dibutyltin dilaurate are added in sequence and mixed evenly. The mixture is then sheeted out.

[0028] (4) Two-stage vulcanization: The first stage vulcanization conditions are 170℃ and 15 MPa, and the vulcanization time is up to the positive vulcanization time. The two-stage vulcanization gradient process is as follows: first, it is treated at 75℃ and 95% relative humidity for 12 hours, and then the temperature is raised to 95℃ and 80% relative humidity for 24 hours to obtain the product.

[0029] Example 3 (1) Pre-modification of filler surface: 100 g of filler with a specific surface area of ​​150 m² 2 / g of nano-silica was added to 1000 mL of deionized water and ultrasonically dispersed for 20 min. 2 g of γ-mercaptopropyltriethoxysilane was added, the pH was adjusted to 4.5 with acetic acid, and hydrolysis was carried out for 30 min to obtain a modified silica dispersion.

[0030] (2) In-situ coating and interfacial grafting: The above dispersion was mixed with chloroprene latex containing 30 g of dry adhesive, and anhydrous ethanol was rapidly added to a volume fraction of 60% under shear stirring at 800 rpm. The pH was adjusted to 8.0 with sodium carbonate, and the mixture was heated to 50°C and reacted for 2 hours. After centrifugation, washing, and vacuum drying at 40°C, the core-shell structure reinforced filler was obtained.

[0031] (3) Mixing: On a two-roll mill, 100 g of chloroprene rubber raw rubber is plasticized, and 20 g of core-shell structure reinforcing filler is added. The mixture is then mixed evenly at a roll temperature of 80°C. 2 g of vinyltrimethoxysilane, 1 g of dicumyl peroxide, and 0.1 g of dibutyltin dilaurate are added in sequence and mixed evenly. The mixture is then sheeted out.

[0032] (4) Two-stage vulcanization: The first stage vulcanization conditions are 160℃ and 10 MPa, and the vulcanization time is up to the positive vulcanization time. The two-stage vulcanization gradient process is as follows: first, it is treated at 70℃ and 90% relative humidity for 6 hours, and then the temperature is raised to 85℃ and 70% relative humidity for 6 hours to obtain the product.

[0033] Comparative Example 1 On a two-roll mill, 100 g of chloroprene rubber raw material is plasticized, and 40 g of unmodified nano silica (specific surface area 180 m²) is added sequentially. 2 The following ingredients were mixed evenly: 5 g zinc oxide, 4 g magnesium oxide, 1 g stearic acid, and 0.5 g accelerator NA-22. The mixture was then sheeted out and vulcanized on a flat vulcanizing machine at 160°C and 12 MPa for the specified vulcanization time to obtain the composite material.

[0034] Comparative Example 2 On a two-roll mill, 100 g of chloroprene rubber raw rubber was plasticized, and 40 g of commercially available unmodified nano silica, 4 g of vinyltrimethoxysilane, 2 g of dicumyl peroxide, and 0.3 g of dibutyltin dilaurate were added sequentially. The mixture was stirred evenly at a roll temperature of 90°C and then sheeted out. The first-stage vulcanization and second-stage vulcanization processes were exactly the same as step (4) in Example 1 to obtain the composite material.

[0035] Comparative Example 3 (1) Preparation of filler: 100 g of filler with a specific surface area of ​​180 m² 2 / g of nano-silica was ultrasonically dispersed in 1000 mL of deionized water, and mixed with chloroprene latex containing 30 g of dry adhesive. Anhydrous ethanol was rapidly added to a volume fraction of 70% under shear stirring at 1200 rpm, causing the chloroprene rubber to precipitate and coat the surface of the nano-silica. γ-mercaptopropyltriethoxysilane was not added, the pH was not adjusted, and the reaction was not heated. The mixture was centrifuged, washed, and vacuum dried at 40℃ to obtain a core-shell packing material with only a physical coating structure.

[0036] (2) Mixing and vulcanization: Mix 40 g of the above-mentioned physically coated core-shell filler with 100 g of chloroprene rubber raw rubber, and then add 4 g of vinyltrimethoxysilane, 2 g of dicumyl peroxide and 0.3 g of dibutyltin dilaurate. The mixing and vulcanization process is exactly the same as steps (3) and (4) in Example 1 to obtain the composite material.

[0037] Comparative Example 4 40 g of the surface-silanized core-shell structure reinforcing filler prepared in step (2) of Example 1 was mixed with 100 g of chloroprene rubber raw rubber on a two-roll mill. 5 g of zinc oxide, 4 g of magnesium oxide, 1 g of stearic acid, and 0.5 g of accelerator NA-22 were added sequentially, and the mixture was mixed evenly and sheeted. The sheet was then vulcanized on a flat vulcanizing machine at 160°C and 12 MPa for the required vulcanization time to obtain the composite material.

[0038] Comparative Example 5 Aminosilane was used as a crosslinking agent, and the filler was not coated. On a two-roll mill, 100 g of chloroprene rubber raw rubber was plasticized, and 40 g of unmodified nano silica, 3 g of γ-aminopropyltriethoxysilane, and 0.5 g of dibutyltin dilaurate were added sequentially. The mixture was stirred until uniform and then sheeted out. The first-stage vulcanization and second-stage vulcanization processes were exactly the same as step (4) in Example 1 to obtain the composite material.

[0039] Performance testing: Tensile strength and elongation at break: Tested in accordance with GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", using dumbbell-shaped type I specimens, with a tensile rate of 500 mm / min.

[0040] Tear strength: Tested in accordance with GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)", using right-angled specimens.

[0041] Dynamic compression fatigue temperature rise: According to GB / T 1687.3-2016 "Determination of temperature rise and fatigue resistance of vulcanized rubber in flexural test", a Goodrich compression fatigue testing machine was used. The test conditions were: stroke 4.45 mm, load 1 MPa, frequency 30 Hz, constant temperature chamber 60℃, test time 25 min, and the temperature rise value at the bottom of the sample was recorded.

[0042] Binder content: Weigh approximately 0.5 g of the sample and place it in a nickel mesh of known mass. Immerse the sample in 100 mL of toluene for 72 hours, replacing the toluene with fresh toluene every 24 hours. Remove the nickel mesh and vacuum dry it at 60°C to constant weight, then weigh it. The binder content is calculated using the following formula: Binder content (%) = [m2 - m1 × (1 - w)] / (m1 × w) × 100%, where m1 is the initial mass of the sample, m2 is the residual mass after drying, and w is the mass fraction of rubber in the formulation.

[0043] Crosslinking density: determined using the equilibrium swelling method. Approximately 0.2 g of sample was swollen in toluene at 25°C for 72 hours until equilibrium was reached. After removal, the surface solvent was quickly wiped off with filter paper, and the mass of the swollen body was weighed. The crosslinking density was calculated using the Flory-Rehner formula.

[0044]

[0045] The surface-silanized core-shell filler prepared by the simultaneous in-situ coating and interface grafting process of this invention, combined with a silane crosslinking system, exhibits significantly superior overall performance compared to the comparative examples. Comparative Example 1 uses a traditional zinc oxide / magnesium oxide vulcanization system, where the filler and matrix only exhibit physical adsorption, with a binder content of only 18.2% and a dynamic compression temperature rise of 32.4℃, resulting in significantly lower mechanical properties. Comparative Examples 2 and 5, although using a silane crosslinking system, did not involve coating or grafting treatment of the filler, resulting in the weakest interfacial bonding, with tensile strengths of only 15.7 MPa and 14.8 MPa, and binder contents of only 15.6% and 14.5%, respectively. This demonstrates that simply replacing the crosslinking system without addressing the filler-matrix interface issue cannot achieve high performance. Comparative Example 3 uses physically coated core-shell filler but without silanization grafting. Although the binder content is higher than the simple blend system, it is still far lower than that of Example 1, and the dynamic compression temperature rise is also higher than that of Example 1, directly demonstrating the crucial role of chemically grafted active groups on the shell surface in constructing covalent interfaces. Comparative Example 4 uses the core-shell filler of the present invention in a traditional metal oxide vulcanization system. Since the alkoxysilane groups on the filler surface cannot participate in the ZnO / MgO crosslinking reaction, the binder content and dynamic compression temperature rise are not as good as in Example 1, but are better than other comparative examples. This verifies that there is a synergistic effect between the silane crosslinking system and the surface silanized core-shell filler, and both are indispensable.

[0046] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. An in-situ coated reinforced silane crosslinked chloroprene rubber composite material, characterized in that, It includes a chloroprene rubber matrix and a core-shell structured reinforcing filler dispersed in the chloroprene rubber matrix; The core-shell structure reinforcing filler includes nano-silica as the core and chloroprene rubber as the shell. The shell layer is grafted with alkoxysilane groups derived from mercaptosilane coupling agents via thioether bonds. The chloroprene rubber matrix and the core-shell structure reinforcing filler are connected through a siloxane crosslinking network formed by the participation of the alkoxysilane groups.

2. The in-situ coated reinforced silane crosslinked chloroprene rubber composite material according to claim 1, characterized in that, The mercaptosilane coupling agent is selected from at least one of γ-mercaptopropyltriethoxysilane and γ-mercaptopropyltrimethoxysilane; In the shell layer, the allyl chloride on the chloroprene rubber molecular chain forms the thioether bond with the mercapto group of the mercaptosilane coupling agent.

3. The in-situ coated reinforced silane crosslinked chloroprene rubber composite material according to claim 1, characterized in that, The specific surface area of ​​the nano-silica is 150-200 m². 2 / g.

4. The in-situ coated reinforced silane crosslinked chloroprene rubber composite material according to any one of claims 1-3, characterized in that, The amount of the core-shell structure reinforcing filler is 20-60% of the chloroprene rubber matrix; The siloxane crosslinking is formed by the hydrolysis and condensation of alkoxysilane groups on the surface of the core-shell structure reinforced filler and an externally added silane crosslinking agent.

5. The in-situ coated reinforced silane crosslinked chloroprene rubber composite material according to claim 4, characterized in that, The added silane crosslinking agent is selected from one or a combination of two of vinyltrimethoxysilane and vinyltriethoxysilane.

6. A method for preparing an in-situ coated reinforced silane crosslinked chloroprene rubber composite material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Disperse nano-silica in water, add mercaptosilane coupling agent for pre-hydrolysis, and obtain modified silica dispersion with alkoxysilane groups grafted on the surface; (2) The modified silica dispersion is mixed with chloroprene latex, and an alcohol precipitant is added under shear stirring to precipitate chloroprene rubber and coat it on the surface of nano silica. At the same time, the pH is adjusted to 8-9 and heated to 50-60℃ for 2-3 hours to obtain a core-shell structure reinforced filler with reactive silane groups on the surface. (3) The core-shell structure reinforcing filler is mixed with chloroprene rubber raw rubber, added silane crosslinking agent, initiator and catalyst at 80-100℃ to obtain a compound; (4) The compound is first vulcanized at 160-170℃ and 10-15 MPa pressure, and then vulcanized at 70-95℃ and 70%-95% relative humidity to obtain the in-situ coated reinforced silane crosslinked chloroprene rubber composite material.

7. The preparation method according to claim 6, characterized in that, In step (1), the amount of the mercaptosilane coupling agent is 2%-5% of the dry weight of the nano-silica.

8. The preparation method according to claim 6, characterized in that, In step (3), the initiator is dicumyl peroxide, and the amount used is 1-3% of the chloroprene rubber matrix.

9. The preparation method according to claim 6, characterized in that, In step (3), the catalyst is dibutyltin dilaurate, and the amount used is 0.1-0.5% of the chloroprene rubber matrix.

10. The preparation method according to claim 6, characterized in that, In step (4), the secondary vulcanization is a gradient vulcanization: first, it is treated at 70-75℃ and 90%-95% relative humidity for 6-12 hours, and then the temperature is raised to 85-95℃ and 70%-80% relative humidity for 6-24 hours.

Citation Information

Patent Citations

  • multi-layer rubber cable

    CN104821197B

  • A chloroprene rubber compound for automobile wiper blades and its preparation method and application

    CN115322462B